(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The available huge amount of solar radiation in Iraq all over the year can be regarded as a useful energy source. It can be utilized to generate electrical energy using PV panel’s power plants. Therefore, it is important to recognize the behavior of these PV Panels through the year with changing in amount of the solar radiation and weather temperature. The monthly average (daily and hourly) of extraterrestrial, global, diffused, and beam radiation, with PV panel’s temperature and electrical efficiency of different tilt angle is studied in three Iraqi’s cities. The results indicated that the total radiation ranges are greater in Karbala than Samarra and Basra cities; despite of the extraterrestrial radiation in Basra higher value than Samarra and Karbala cities. The higher magnitude in the monthly average solar radiation in any city is not necessarily best location for construction PV power plant, because the electrical performance of PV panels is affected by its temperature. Rising in temperature led to drop in the PV panel’s efficiency.